ANALISIS STRUKTURAL PADA CERPEN SEMAR KARYA PUTU WIJAYA DALAM KOMPAS 2023 - Puji, Puji Adi Pertiwi; Sari, Miranda; Harahap, Rosminah; Rianza, Dika (Universitas PGRI Palembang, 2025)
This study aims to gain a comprehensive understanding of the intrinsic elements within the short story Semar. The intrinsic elements analyzed include theme, character, characterization, setting, plot, moral message, and language style. A qualitative descriptive method was employed in this research, as it enables an in-depth depiction and analysis of the structural elements based on textual data. The research process involved repeatedly reading the short story Semar to grasp its nuances and finer details. During this process, the researcher highlighted and took notes on sentences or quotations relevant to the intrinsic elements under examination. The findings indicate that Semar presents a strong central theme, focusing on moral values and the human condition. The characters are portrayed with depth, and the characterization reflects the complexity of human nature and the internal conflicts they experience. This analysis not only sheds light on the structural composition of Semar but also illustrates how the intrinsic elements cohesively interact to produce a meaningful literary work. Such analysis is essential for enhancing literary appreciation and for assisting readers in understanding the author’s intended message.